EARNINGS MANAGEMENT AROUND ADDITIONAL SHARE OFFERING EVENTS - Andreas Vernando; Sumaryanto Sumaryanto (Universitas Airlangga, 2019)
Additional stock offerings are a determinant of a company's earnings management (Teoh et al., 1998b; Rangan 1998; Shivakumar 2000; Kim and Park 2005; Cohen and Zarowin 2010). However, the results of previous studies are not in line with the results of Ball and Shivakumar (2008). Ball and Shivakumar (2008) argue that companies do not conduct earnings management before conducting an initial public offering because there are good regulations in the US and UK. Strong oversight mechanisms such as those in the US and UK may not apply in Indonesia. Cheung et al., (2014) used a survey instrument to assess the quality of corporate governance practices in Asian Emerging Markets. The results of the research by Cheung et al., (2014) provide evidence that Indonesia is a country that has the worst Corporate Governance Index among China, Hong Kong, Thailand and the Philippines. The difference between this study and previous research is that in addition to using different test analysis, this study uses regression analysis to obtain more comprehensive results. This study uses the Wilcoxon signed rank test analysis tool to compare accrual and real earnings management before and after the additional share offering. In addition, this study uses multiple regression analysis to detect whether additional stock events affect earnings management by including other determinant variables. The results of the different test show that the company uses accrual and real earnings management at the time of additional stock events. To get a more robust picture of the results (robust), this study uses multiple regression analysis. The results of multiple regression analysis provide similar evidence that companies use accrual and real earnings management at the time of additional stock events, after controlling for other determinant variables.